2002
DOI: 10.2320/matertrans.43.1833
|View full text |Cite
|
Sign up to set email alerts
|

Melting and Joining Behavior of Sn/Ag and Sn-Ag/Sn-Bi Plating on Cu Core Ball

Abstract: We fabricated Cu core Sn-Ag solder balls by plating pure Sn and Ag on Cu balls and clarified that Sn/Ag plating began to melt at a rather low temperature, the eutectic temperature of Sn-Ag-Cu. This early melting at the eutectic temperature was ascribed to the diffusion of Cu and Ag into the Sn plating during the heating process. We investigated the solderability of the BGA joint with the Ni/Au coated Cu pad to compare it with that of the commercial Sn-Ag and Sn-Ag-Cu balls. After reflow soldering, we observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Similar to the literature results, [21][22][23] this study finds that the usage of a Cu-cored solder ball can effectively inhibit regrouping of the (Au x Ni 1Àx )Sn 4 phase in the BGA solder joint. In addition, it is also shown that the inhibition is effective for the Cu core of diameters ranging from 500 mm to 700 mm.…”
Section: Solid-state Annealingsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the literature results, [21][22][23] this study finds that the usage of a Cu-cored solder ball can effectively inhibit regrouping of the (Au x Ni 1Àx )Sn 4 phase in the BGA solder joint. In addition, it is also shown that the inhibition is effective for the Cu core of diameters ranging from 500 mm to 700 mm.…”
Section: Solid-state Annealingsupporting
confidence: 90%
“…However, the size effect is not discussed in the previous studies. [21][22][23] Therefore, three sizes of the Cu sphere, 500 mm, 650 mm, and 700 mm, are used in this study to fabricate the Cu-cored solder ball that has a common diameter, 760 mm, and by which the size effect of the Cu sphere is examined. Eutectic SnPb solder alloy is used to form the outer layer of the Cu-cored solder ball.…”
Section: Introductionmentioning
confidence: 99%
“…2, 3) The implicit requirements for industrialization of the copper spherical particle are its size variation, size controllability, size uniformity and mass-productivity. Since the demanded particle size is dependent on the latest particle array technique, the necessary size variation in future would be at least down to below 100 mm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a Cu core ball is a candidate for high-power and high-performance applications. 18 A smaller size of core ball, less than 100 lm, is required for the chip-scale package. In view of the difficulty of producing a Cu core ball with a size of <100 lm, an egg-type core solder ball can be obtained by a very simplified fabrication method, as shown in Fig.…”
Section: Powder Of Pb-free Soldersmentioning
confidence: 99%